2015
DOI: 10.1016/j.bbi.2014.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Salivary markers of inflammation in response to acute stress

Abstract: There is burgeoning interest in the ability to detect inflammatory markers in response to stress within naturally occurring social contexts and/or across multiple time points per day within individuals. Salivary collection is a less invasive process than current methods of blood collection and enables intensive naturalistic methodologies, such as those involving extensive repeated measures per day over time. Yet the reliability and validity of saliva-based to blood-based inflammatory biomarkers in response to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
209
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(218 citation statements)
references
References 132 publications
(303 reference statements)
5
209
1
3
Order By: Relevance
“…Furthermore, our findings suggest that maternal distress is related to differences in some, but not all, salivary inflammatory mechanisms examined; further research is needed to understand the sensitivity of specific NEI relations to psychosocial factors. Future research should investigate NEI relations using other markers of inflammation, such as C-reactive protein, which has been found to have stronger serum-saliva correlations than other inflammatory markers (Slavish et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, our findings suggest that maternal distress is related to differences in some, but not all, salivary inflammatory mechanisms examined; further research is needed to understand the sensitivity of specific NEI relations to psychosocial factors. Future research should investigate NEI relations using other markers of inflammation, such as C-reactive protein, which has been found to have stronger serum-saliva correlations than other inflammatory markers (Slavish et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…While salivary cytokine activity likely reflects local immune processes, interactions between inflammatory cytokine and HPA activity in the oral cavity have been found to mirror immune-HPA relations previously identified in serum (Riis et al, 2015). Furthermore, in studies of adults, salivary IL-1β, IL-6 and TNF-α have exhibited acute stress sensitivity (Slavish, Graham-Engeland, Smyth, & Engeland, 2015). …”
Section: Methodsmentioning
confidence: 99%
“…Heart; blood Stress duration dependent " plasma CORT; ; heart histamine level; " serum histamine level; " mast cell degranulation Huang et al " plaque size; " hematopoietic system activity; " plaque protease levels; " intimal neutrophils, monocytes and macrophages; " necrotic core area; ; fibrous cap thickness; " plaque monocyte inflammatory gene expression No significant difference in bodyweight; total cholesterol Dutta et al (2012) Similar to the response to chronic stress, acute stress exposure has been demonstrated to result in a quick rise in plasma interleukins and inflammatory markers (Table 1) (Yamauchi et al, 2013;Wilbert-Lampen et al, 2010;Schultze-Florey et al, 2012;Cohen et al, 2015;Suarez, 2004;Coccaro et al, 2014;Slavish et al, 2015), such as IL-6, IL-1b and sICAM (Heinz et al, 2003;Kuebler et al, 2015), which have all been demonstrated to be proatherogenic. Furthermore, the rise in plasma IL-6 was seen to associate with fibrin formation and pro-coagulant markers (von Känel et al, 2005), which may lead to an enhanced risk of thrombosis upon plaque rupture.…”
Section: Acute Stress and Acute Cardiovascular Syndromesmentioning
confidence: 93%
“…Immediately before and after the first and final sessions of the 6-week intervention, participants completed visual analogue mood scales, blood pressure measurements and provided a saliva sample, collected via passive drool method and stored immediately at -20°C. Recent research has documented the promise of salivary measurement in psychobiological research as a non-invasive, pain-free tool [8,9,10]. Saliva samples were analysed using Luminex multiplex assays.…”
Section: Tablementioning
confidence: 99%